2006
DOI: 10.1128/aac.00012-06
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bacterial Acetyl Coenzyme A Carboxylase Inhibitors with Antibiotic Efficacy In Vivo

Abstract: The pseudopeptide pyrrolidinedione antibiotics, such as moiramide B, have recently been discovered to target the multisubunit acetyl coenzyme A (acetyl-CoA) carboxylases of bacteria. In this paper, we describe synthetic variations of each moiety of the modularly composed pyrrolidinediones, providing insight into structure-activity relationships of biochemical target activity, in vitro potency, and in vivo efficacy. The novel derivatives showed highly improved activities against gram-positive bacteria compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
56
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 13 publications
3
56
1
1
Order By: Relevance
“…However, the molecular basis for the differential susceptibility of Gram-positive pathogens to FASII inhibitors has been uncovered, providing an understanding of why FASII inhibitors are effective against S. aureus even in the presence of an extracellular source of fatty acids (7). These data resolved the debate concerning the validity of using fatty acid synthesis inhibitors to treat S. aureus infections (8,9) and are consistent with the examples of fatty acid synthesis inhibitors that show efficacy in S. aureus-infected animal models (5,8,(10)(11)(12)(13)(14).…”
supporting
confidence: 56%
“…However, the molecular basis for the differential susceptibility of Gram-positive pathogens to FASII inhibitors has been uncovered, providing an understanding of why FASII inhibitors are effective against S. aureus even in the presence of an extracellular source of fatty acids (7). These data resolved the debate concerning the validity of using fatty acid synthesis inhibitors to treat S. aureus infections (8,9) and are consistent with the examples of fatty acid synthesis inhibitors that show efficacy in S. aureus-infected animal models (5,8,(10)(11)(12)(13)(14).…”
supporting
confidence: 56%
“…2c) because substitution of the valine in andrimid with other aliphatic amino acids does not disrupt its antibacterial activity (27), whereas replacement of its ␤-phenylalanine or its glycinederived succinimide abrogates activity (26). We constructed a knockout of the admK gene (admK::cat) in a cosmid expressing the andrimid gene cluster and confirmed that a plasmid-borne admK gene complements this knockout (SI Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Because previous work had shown that substituting isoleucine for valine confers increased potency on a synthetic derivative of andrimid (27), we constructed a second AdmK chimera by replacing AdmK-A with the isoleucine-specific BacA-A1 domain from the Bacillus licheniformis bacitracin NRPS (29). Complementation of the admK::cat strain with plasmid-encoded AdmK-BacA-A1 generated the corresponding isoleucine-containing derivative of andrimid (6) with a 7-fold reduction in product yield compared with that of the wild-type enzyme (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6B-6F), whereas several previously reported interactions were recapitulated in the Y. pestis PPi network (Fig. 6B, 6D, 6E) (35)(36)(37). Of the annotated proteins within the network (n ϭ 218), one-quarter could be mapped to a protein class (Fig.…”
Section: Resultsmentioning
confidence: 67%